Pengaruh Kualitas Layanan terhadap Loyalitas melalui Kepuasan Konsumen Studi pada Trans Sarbagita - Hilmawan, Irvan Made; Suryani, Alit (E-Jurnal Manajemen, 2014)
Trans Sarbagita is a provider of transportation services who attended to resolve the traffic problems that occurred in Bali. Services quality provided by Trans Sarbagita greatly affects customer satisfaction and loyalty. Knowing the effect that the service quality to customer loyalty through customer satisfaction as an intervening variable in the Trans Sarbagita is the purpose of this research. The questionnaire is a data collection techniques used. The research used a sample of 100 respondents drawn through purposive sampling technique. Path analysis is a method of analysis used in this research. Path analysis is useful to determine the direct and indirect effects that occur between variables. The results from this research is the service quality has influence directly and indirectly through consumer satisfaction on consumer loyalty.
Keywords: Service Quality, Customer Satisfaction, Customer Loyalty